Global trends and hotspots in diabetes and obesity research: A bibliometric analysis - Xian Wang; Jinhu Chen; Qiuyu Bai (Journal of Family Medicine and Primary Care)
Diabetes and obesity are major global public health challenges, with their incidence continuously rising, placing a significant burden on healthcare systems worldwide. To better understand the research trends and hotspots in these two areas, this study conducted a bibliometric analysis of relevant literature published between 2003 and 2023. The study utilized the Web of Science Core Collection database to select original research articles and reviews on diabetes and obesity published from 2003 to 2023. CiteSpace and R software were employed for bibliometric analysis, including co-occurrence analysis of keywords, co-citation analysis, and collaboration network analysis. Research on diabetes and obesity has seen significant growth globally, with the United States, China, and the United Kingdom being the most active countries in this field. The transnational collaboration network is expanding, especially between Europe, the United States, and Asia. Research hotspots include lifestyle interventions, weight management, and nutritional interventions. Future research should focus on international collaboration and interdisciplinary approaches, particularly in clinical practice for primary care physicians. Personalized lifestyle interventions and management strategies for diabetes and obesity represent key areas for further exploration.